Social media usage for tv viewing in China : predictors, media engagement, and user behavior - Liang, Ziqi (2016)
The increasing popularity of using social media for TV-related matters can have a positive effect on TV ratings and audience engagement. According to Kantar Media (2014), more than 50% of TV audiences in China posted their opinions related to popular TV programs on Weibo. As the degree of social media discussions turns into TV metrics (Smitha, 2013), Weibo TV Rating Index improves the assessment of TV program performance in addition to ratings. Despite the hype of using social media for TV-related matters, there is little scholarly research in this emerging area.